2019
DOI: 10.1177/1550059419867561
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Versus Nondeficit Schizophrenia: An MEG-EEG Investigation of Resting State and Source Coherence—Preliminary Data

Abstract: This study investigated the magneto- and electroencephalography (MEG and EEG, respectively) resting state to identify the deviations closely associated with the deficit syndrome (DS) in schizophrenia patients. Ten subjects in each group (control, DS, and nondeficit schizophrenia [NDS]) were included. Subjects underwent MEG-EEG recordings during a resting state condition. MEG coherence source imaging (CSI) in source space and spectral analysis in sensor space were performed. Significant differences were found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…Although we cannot directly compare the previous results shown by power spectral density with the current results shown by PCA, the direction in which increases are shown from theta through gamma bands in the current study is consistent to the previous studies with eyes-open conditions (17,(46)(47)(48). Relevant to gamma-band power, while a previous resting-state MEG study with eyes-open condition by Grent-'t-Jong et al (21) showed an increased gamma power (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) at the occipital cortex and a decreased at the prefrontal cortex in first episode schizophrenia patients (N = 21), they demonstrated a decreased gamma power at the frontal, temporal, and sensorimotor cortices in chronic schizophrenia patients (N = 34) compared to healthy controls (N = 37). Inconsistency of their results (21) and our findings of elevated gamma-band power in chronic schizophrenia patients may be due to the difference of clinical stages.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although we cannot directly compare the previous results shown by power spectral density with the current results shown by PCA, the direction in which increases are shown from theta through gamma bands in the current study is consistent to the previous studies with eyes-open conditions (17,(46)(47)(48). Relevant to gamma-band power, while a previous resting-state MEG study with eyes-open condition by Grent-'t-Jong et al (21) showed an increased gamma power (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) at the occipital cortex and a decreased at the prefrontal cortex in first episode schizophrenia patients (N = 21), they demonstrated a decreased gamma power at the frontal, temporal, and sensorimotor cortices in chronic schizophrenia patients (N = 34) compared to healthy controls (N = 37). Inconsistency of their results (21) and our findings of elevated gamma-band power in chronic schizophrenia patients may be due to the difference of clinical stages.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, gamma-band power was not reported. While some studies showed increased resting-state gamma-band power in schizophrenia in eyes-closed condition (18)(19)(20), Grent-'t-Jong et al (21) found an increased gamma power (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) at the occipital cortex and a decreased at the prefrontal cortex in first episode schizophrenia patients (N = 21) and showed a decreased MEG gamma power at the frontal, temporal, and sensorimotor cortices in chronic schizophrenia patients (N = 34) compared to healthy controls (N = 37).…”
Section: Introductionmentioning
confidence: 99%